Correlation among vigor tests on gherkin seeds - Torres, Salvador Barros; da Silva, Magnólia Aparecida Silva; de Carvalho, Ione Maria Soares; de Queiróz, Manoel Abílio (Pesquisa Agropecuaria Brasileira, 1999)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> This work was carried out with the objective of comparing the efficiency of different tests in the physiological quality of gherkin seeds (Cucumis anguria L.), looking for information for a better utilization of these quality control tests, as well as verifying their relation at field emergency. Seven lots of gherkin seeds were evaluated by the germination test, first count, electrical conductivity at 4 and 24 hours, accelerated aging, controlled damage, cold without soil, and field emergency. The trials were carried out at the Seed Lab and at an experimental field of Embrapa-CPATSA, at Petrolina, PE, Brazil, from January to May 1996. In the lab tests, a completely randomized design was used, and in the field tests, a randomized block design was used - both of them with four repetitions of fifty seeds, being the means compared by the Tukey test, at 1% of probability. The germination and vigor tests were effective to detect differences of physiological quality among gherkin seed lots. The damage control and cold without soil tests were more stable on the division of the lots by the vigor levels and, at the same time, showed the highest correlation with field emergency.